Method for preparing nanometer aluminum oxide coating on surface of 310S stainless steel
Through ALD technology, nano alumina coating is deposited layer by layer on the surface of 310S stainless steel, which solves the problems of poor coating uniformity and weak adhesion in the prior art, and realizes efficient preparation of uniform and dense coatings on complex shape surfaces, significantly improving 310S The high temperature oxidation resistance and corrosion resistance of stainless steel.
Patent Information
- Application Number
- CN202411336408.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-03
Smart Images

Figure CN119243116A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inert nano coating preparation, and specifically relates to a method for preparing a nano aluminum oxide coating on the surface of 310S stainless steel. Background Art
[0002] 310S stainless steel has excellent antioxidant and corrosion resistance. Therefore, this type of stainless steel is often used in high-temperature equipment, such as heat exchangers, high-temperature furnaces, petrochemicals, energy, aerospace and many other fields. However, due to long-term high-temperature working environment, the surface of the 310S substrate is inevitably corroded by oxidation, resulting in component damage and shortened life. On the other hand, the Cr element diffuses to the surface of the substrate at high temperature and is converted into volatile high-valent chromium compounds, which are highly toxic and harmful to human health and instruments. In addition, chloride ions (Cl - ) has strong corrosion effects on 310S stainless steel, especially in terms of pitting corrosion and crevice corrosion, which seriously restricts the application of 310S stainless steel in such environments.
[0003] In the prior art, the oxidation resistance and corrosion resistance of stainless steel are improved by adding alloying elements such as Al, Si and Ti, but this also changes the mechanical properties and working performance of stainless steel. In recent years, the method of changing the surface properties of metals by coating has been widely studied. Al2O3 coating has good stability, chemical inertness, high temperature resistance and corrosion resistance, making it an ideal choice for protecting stainless steel from high temperature oxidation and chemical corrosion.
[0004] So far, there are many methods for preparing Al2O3 coatings on the surface of stainless steel, including plasma spraying, chemical vapor deposition (CVD), physical vapor deposition (PVD, such as evaporation and sputtering), sol-gel method and electrodeposition, among which: the uniformity and adhesion of Al2O3 coatings prepared by plasma spraying are poor, the film thickness is difficult to control during the preparation process, and the substrate is easily damaged due to excessive temperature; CVD usually needs to prepare Al2O3 coatings under high temperature conditions, and the preparation process is relatively complicated; the rate of Al2O3 coatings prepared by PVD is low, and residual stress may exist, especially on substrates with complex shapes, which affects the coating performance; the Al2O3 coatings prepared by the sol-gel method have limited coating thickness and uniformity, usually require multiple coatings and heat treatments, the process of preparing the coating is difficult, and the coating adhesion is weak and easy to peel off; the Al2O3 coatings prepared by electrodeposition have poor adhesion, uniformity and density. In summary, the nano-Al2O3 coating prepared by the above method has the problems of low precision, poor uniformity, weak adhesion, insufficient density, complex preparation process and difficulty in preparation on a substrate with complex shape. Summary of the invention
[0005] The main purpose of the present invention is to overcome the deficiencies in the prior art and solve the technical problem of preparing a uniform and dense nano-Al2O3 coating on the surface of 310S stainless steel with simple process, high precision, strong adhesion and conformality. The present invention provides a method for preparing a nano-alumina coating on the surface of 310S stainless steel.
[0006] The present invention is implemented by the following technical scheme: A method for preparing a nano-aluminum oxide coating on the surface of 310S stainless steel comprises the following steps: S1. Substrate pretreatment: S1-1, using a wire cutting machine to cut the SUS 310S stainless steel plate into substrates with a size of 15 mm in length × 15 mm in width × 1.5 mm in thickness; S1-2, using 120 mesh, 240 mesh, 400 mesh and 600 mesh sandpaper to polish the surface of the substrate prepared in step S1-1; S1-3, placing the polished substrate in step S1-2 into beakers containing water and anhydrous ethanol in turn for ultrasonic cleaning, with the ultrasonic cleaning time being 20 min each, and then placing the cleaned substrate in a vacuum drying oven for constant temperature storage for later use; S2. Preparation of hydroxyl active sites on the substrate surface: placing the substrate pretreated in step S1 into the ALD chamber, injecting O3 into the ALD chamber by pulses at a flow rate of 50-200 sccm, and maintaining the O3 gas atmosphere for 20-30 seconds to construct hydroxyl active sites on the substrate surface; S3, ALD atomic layer deposition: using a mixed solution of trimethylaluminum and deionized water as a precursor, using the ALD atomic layer deposition process to prepare a nano-aluminum oxide film on the surface of the substrate, the temperature in the ALD chamber is 150°C, and the pressure in the ALD chamber is 10~100 mbar; S4, pulse injection of trimethylaluminum solution into the ALD chamber, the pulse injection time is 0.015s, the flow rate is 1-10sccm, and then exposed in the trimethylaluminum solution atmosphere for 5s, the trimethylaluminum solution reacts with the hydroxyl active sites on the surface of the substrate to form a single molecule covered aluminum precursor layer, and then the unreacted trimethylaluminum solution and by-products are purged by high-purity nitrogen; repeat this step S4 alternately pulse injection and purging, the frequency is 1-10Hz; S5, pulse injection of deionized water into the ALD chamber, the pulse injection time is 0.1s, the flow rate is 1-10sccm, the water molecules react with the TMA molecular layer adsorbed on the surface of the substrate to form an aluminum oxide coating and release by-products, and the residues are purged again by high-purity nitrogen; repeat this step S5 alternately pulse injection and purging, the frequency is 1-10Hz; S6, repeating steps S2, S4 and S5, preparing the Al2O3 coating layer by layer and accurately controlling the thickness of the Al2O3 coating until a uniform and dense nano-Al2O3 coating with a thickness meeting a predetermined requirement is formed on the surface of the substrate; S7. Take out the substrate covered with the nano-alumina coating prepared in step S6, heat it to an ultra-high temperature of 1000° C. to 1200° C. and keep the temperature constant for 10 h to 50 h to obtain 310S stainless steel covered with the nano-alumina coating.
[0007] The beneficial effects of the present invention are: 1) The present invention prepares a nano-Al2O3 coating on the surface of 310S stainless steel by ALD atomic layer deposition process, which not only solves the problem of equipment damage and volatilization of toxic high-valent Cr caused by oxidation of 310S stainless steel in a high-temperature working environment for a long time, but also solves the problem of Cl in 310S stainless steel in a short-term working environment such as salt water. - In order to solve the corrosion problem, compared with the traditional preparation method, ALD technology can obtain a uniform and dense nano-Al2O3 film on the surface of 310S stainless steel through one-step deposition. The process is relatively simple and efficient. Moreover, ALD technology can accurately control the thickness of the nano-Al2O3 coating, deposit layer by layer, and has strong adhesion.
[0008] 2) The present invention adopts the ALD atomic layer deposition process to deposit a uniform and dense nano-Al2O3 film on the stainless steel surface with complex shapes, thereby meeting the use of 310S stainless steel in any working conditions.
[0009] 3) Before each deposition cycle, the present invention forms new hydroxyl sites on the surface by cyclically injecting O3, providing sufficient chemical reaction sites for the precursor reaction of the next cycle, thereby improving the reaction activity and film quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 The 310S-ALD Al2O3 sample prepared by the present invention and the scanning electron microscope image after oxidation; Figure 2 The X-ray diffraction pattern of the 310S-ALD Al2O3 sample prepared by the present invention and its oxidation; Figure 3 The X-ray photoelectron spectrum of the 310S-ALD Al2O3 sample prepared by the present invention and its oxidation; Figure 4 This is the narrow spectrum of X-ray photoelectron energy spectrum of Cr element in the surface of oxidized 310S-ALD Al2O3 sample; Figure 5 This is the polarization curve of the 310S-ALD Al2O3 sample prepared in the present invention. DETAILED DESCRIPTION
[0011] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0012] A method for preparing a nano-aluminum oxide coating on the surface of 310S stainless steel comprises the following steps: S1. Substrate pretreatment: S1-1, using a wire cutting machine to cut the SUS 310S stainless steel plate into substrates with a size of 15 mm in length × 15 mm in width × 1.5 mm in thickness; S1-2, using 120 mesh, 240 mesh, 400 mesh and 600 mesh sandpaper to polish the surface of the substrate prepared in step S1-1; S1-3, placing the polished substrate in step S1-2 into beakers containing water and anhydrous ethanol in turn for ultrasonic cleaning, with the ultrasonic cleaning time being 20 min each, and then placing the cleaned substrate in a vacuum drying oven for constant temperature storage for later use; S2. Preparation of hydroxyl active sites on the substrate surface: Place the substrate pretreated in step S1 into the ALD chamber, pulse inject O3 into the ALD chamber at a flow rate of 200 sccm, and maintain the O3 gas atmosphere for 30 seconds to allow the substrate surface to react with O3 and construct hydroxyl active sites on the substrate surface; S3, ALD atomic layer deposition: using a mixed solution of trimethylaluminum (Al(CH3)3, TMA) and deionized water (H2O) as a precursor, the ALD atomic layer deposition process was used to prepare a nano-aluminum oxide film on the surface of the substrate. The temperature in the ALD chamber was 150°C and the pressure in the ALD chamber was 100 mbar. S4, pulse injection of trimethylaluminum solution into the ALD chamber, the pulse injection time is 0.015s, the flow rate is 1-10sccm, and then exposed in the trimethylaluminum solution atmosphere for 5s, the trimethylaluminum solution reacts with the hydroxyl active sites on the surface of the substrate to form a single molecule covered aluminum precursor layer, and then high-purity nitrogen (50sccm) is used to purge and remove the unreacted trimethylaluminum solution and by-products; repeat this step S4, alternately pulse injection and purge, the frequency is 5Hz; S5, pulse injection of deionized water into the ALD chamber, the pulse injection time is 0.1s, the flow rate is 10sccm, the water molecules react with the TMA molecular layer adsorbed on the surface of the substrate to form an aluminum oxide coating and release by-products, and the residues are removed again by high-purity nitrogen purge (25s); repeat this step S5, alternately pulse injection and purge, the frequency is 5Hz; S6, repeating steps S2, S4 and S5 for 1000 cycles, preparing the Al2O3 coating layer by layer and accurately controlling the thickness of the Al2O3 coating, until a uniform and dense nano-Al2O3 coating with a thickness meeting a predetermined requirement is formed on the surface of the substrate; S7. Take out the substrate covered with the nano-alumina coating prepared in step S6, put it into different crucibles and mark them, then put them into muffle furnaces respectively, raise the temperature to 1200°C at a heating rate of 5°C / min in an air atmosphere, and finally oxidize at a constant temperature for 10h, 20h, 30h, 40h and 50h respectively; when the set time is reached, turn off the muffle furnace, take out the sample after cooling, and obtain 310S stainless steel covered with nano-alumina coating.
[0013] The 310S-ALDAl2O3 coating sample prepared in Example 1 was tested by X-ray diffractometer (XRD) and scanning electron microscope (SEM). Figure 1 and Figure 2 As shown. In the image magnified 200 times, the 310S-ALD Al2O3 coating presents a uniform, smooth, and relatively dense oxide film. The surface scratches of the 310S-ALD Al2O3 coating are significantly reduced compared to before deposition. After the 310S-ALD Al2O3 coating was oxidized at 1200 °C for 10h, 20h, and 30h, the surface oxide film was still relatively dense, without cracks or peeling. After the 310S-ALD Al2O3 coating was oxidized at 1200 °C for 40h and 50h, the surface oxide film peeled off in some areas, but the oxide film as a whole was still relatively intact. Figure 2 It can be seen that the oxide film structure of the 310S-ALD Al2O3 coating is mainly composed of α-Al2O3, γ-Al2O3 and FeAl. When the amorphous 310S-ALD Al2O3 coating is oxidized at 1200 ℃, the diffraction peak of the Al2O3 crystalline component appears, which is mainly composed of α-Al2O3 phase and a small amount of γ-Al2O3 phase. In addition, in the 310S-ALD Al2O3 coating before oxidation, except for the substrate peak of FeCr(Ni), there are no other crystalline peaks representing the film. This is because the deposited Al2O3 is less and the deposited Al2O3 is amorphous, mainly showing a wide range of diffuse peaks (such as at 75.36 °). When the oxidation time reaches 10 h, the diffraction peak intensity of Cr2O3 and MnCr2O4 in the 310S-ALD Al2O3 coating is very low, such as at 33.76 ° and 56.72 °. With the increase of oxidation time, the diffraction peak intensity of Cr2O3 and MnCr2O4 in the 310S-ALD Al2O3 coating increases, but the increase is low, which indicates that the Al2O3 coating deposited using ALD technology has better oxidation resistance.
[0014] The 310S-ALD Al2O3 coating sample was tested by X-ray photoelectron spectroscopy (XPS), and the peak fitting was performed using XPSPEAK41 software. The test results were analyzed as follows: Figure 3 and Figure 4 As shown. Figure 3 It can be seen that before oxidation, the Fe, Ni and Cr peaks on the surface of the 310S-ALD Al2O3 coating sample disappeared, indicating that the Al2O3 coating has been evenly coated on the surface of the 310S stainless steel. With the increase of oxidation time, the relative content of Cr in the 310S-ALD Al2O3 coating continues to increase, but the overall growth trend of the 310S-ALD Al2O3 coating is slow. Figure 4 It can be seen that with the increase of oxidation time, the Cr 3+ To Cr 6+ Conversion, but Cr 6+ Therefore, the 310S-ALD Al2O3 coating has the advantages of preventing Cr from diffusing to the substrate surface and Cr 3+ To Cr 6+ The transformation aspect shows effective Cr resistance, which is beneficial for 310S stainless steel to work at high temperature.
[0015] The electrochemical corrosion experiment was carried out using a three-electrode electrochemical cell. Platinum sheet and saturated calomel electrode (SCE) were used as counter electrode and reference electrode respectively, and the treated 310S substrate and 310S-ALD Al2O3 coating samples were used as working electrodes. The corrosion solution used was a 3.5% NaCl solution.
[0016] The 310S-ALD Al2O3 coating sample was used as the working electrode in the electrochemical experiment and the experimental route was connected. All electrochemical experiments were carried out at room temperature.
[0017] 310S-ALD Al2O3 sample with an exposed working area of 2.25 cm 2 , rinse the surface with distilled water and alcohol, blow dry it immediately, and then transfer it to a corrosion tank filled with electrolyte as described above to avoid the formation of oxides in the air.
[0018] Before the electrochemical polarization measurement, the open circuit potential measurement was performed for 1 hour to obtain a relatively stable potential. The test results of the polarization curve (an important parameter for evaluating the corrosion resistance of the sample) are as follows: Figure 5 As shown. Figure 5 It can be seen that the open circuit potential (OCP) of the 310S-ALD Al2O3 coating is about 0.1 V relative to the saturated calomel electrode (SCE), and the corrosion current density is about 1×10 -5 A / cm2 the following.
[0019] On this basis, in order to further illustrate that the nano-Al2O3 coating prepared on the surface of 310S of the present invention greatly improves the performance of 310S, the following performance comparison experiments are carried out respectively: (1) The 310S substrate and 310S-ALD Al2O3 coating samples before and after high-temperature oxidation were weighed using an electronic scale with an accuracy of 0.0001 g, and the oxidation kinetics of the two were calculated using the Pilling-Bedworth equation; (2) XPS was used to semi-quantitatively analyze the Cr element in the surface of the 310S substrate and 310S-ALD Al2O3 coating samples after high temperature oxidation; XPSPEAK41 software was used to perform peak fitting on the Cr element in the surface of the 310S substrate and 310S-ALD Al2O3 coating samples after high temperature oxidation; (3) Electrochemical corrosion experiments were carried out using a three-electrode electrochemical cell. Platinum sheet and saturated calomel electrode (SCE) were used as counter electrode and reference electrode, respectively, and the treated 310S substrate and 310S-ALD Al2O3 coating samples were used as working electrodes, respectively. The corrosion solution used was a 3.5% NaCl solution. After the experimental route was connected at room temperature, the surface was rinsed with distilled water and alcohol and immediately dried, and then transferred to a corrosion cell filled with electrolyte as described above; the polarization curves of the 310S substrate and 310S-ALD Al2O3 coating samples were analyzed using EC-Lab analysis software.
[0020]
[0021] As shown in Table 1. First, the oxidation rate of the 310S-ALD Al2O3 coating sample is 3.03×10 -12 g 2 cm -4 ·s -1 , which is one order of magnitude lower than that of the 310S substrate; secondly, the Cr and Cr 6+ The contents are 9.67% and 5.73% respectively, which are much lower than the Cr and Cr on the surface of 310S matrix. 6+ In addition, the corrosion current density of the 310S-ALD Al2O3 coating sample in 3.5 wt.% NaCl solution is less than 1×10 -5 A / cm 2 , which is lower than the corrosion current density of 310S substrate. These experimental results show that the nano-Al2O3 coating prepared on the surface of 310S stainless steel by ALD technology has excellent high temperature oxidation resistance, Cr resistance and corrosion resistance.
[0022] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A method for preparing a nano-alumina coating on the surface of 310S stainless steel, characterized in that: The following steps are involved: S1. Substrate pretreatment: S1-1, using a wire cutting machine to cut the SUS 310S stainless steel plate into substrates with a size of 15 mm in length × 15 mm in width × 1.5 mm in thickness; S1-2, using 120 mesh, 240 mesh, 400 mesh and 600 mesh sandpaper to polish the surface of the substrate prepared in step S1-1; S1-3, placing the polished substrate in step S1-2 into beakers containing water and anhydrous ethanol in turn for ultrasonic cleaning, with the ultrasonic cleaning time being 20 min each, and then placing the cleaned substrate in a vacuum drying oven for constant temperature storage for later use; S2. Preparation of hydroxyl active sites on the substrate surface: placing the substrate pretreated in step S1 into the ALD chamber, injecting O3 into the ALD chamber by pulses at a flow rate of 50-200 sccm, and maintaining the O3 gas atmosphere for 20-30 seconds to construct hydroxyl active sites on the substrate surface; S3, ALD atomic layer deposition: using a mixed solution of trimethylaluminum and deionized water as a precursor, using the ALD atomic layer deposition process to prepare a nano-aluminum oxide film on the surface of the substrate, the temperature in the ALD chamber is 150°C, and the pressure in the ALD chamber is 10~100 mbar; S4, pulse injection of trimethylaluminum solution into the ALD chamber, the pulse injection time is 0.015s, the flow rate is 1-10sccm, and then exposed in the trimethylaluminum solution atmosphere for 5s, the trimethylaluminum solution reacts with the hydroxyl active sites on the surface of the substrate to form a single molecule covered aluminum precursor layer, and then the unreacted trimethylaluminum solution and by-products are removed by purging with high-purity nitrogen; Repeat step S4 to alternately pulse injection and purge, with a frequency of 1 to 10 Hz; S5, pulse injection of deionized water into the ALD chamber, the pulse injection time is 0.1s, the flow rate is 1-10sccm, the water molecules react with the trimethylaluminum molecular layer adsorbed on the surface of the substrate to form an aluminum oxide coating and release by-products, and the residues are purged again by high-purity nitrogen; repeat this step S5 alternately pulse injection and purging, the frequency is 1-10Hz; S6, repeating steps S2, S4 and S5, preparing the Al2O3 coating layer by layer and accurately controlling the thickness of the Al2O3 coating until a uniform and dense nano-Al2O3 coating with a thickness meeting a predetermined requirement is formed on the surface of the substrate; S7. Take out the substrate covered with the nano-alumina coating prepared in step S6, heat it to an ultra-high temperature of 1000° C. to 1200° C. and keep it at a constant temperature for 10 h to 50 h to obtain 310S stainless steel covered with the nano-alumina coating.
Citation Information
Cited By
Stainless steel material containing Al2O3 coating and preparation method thereof
CN119877062A
A kind of Al 2 O 3 Coated stainless steel material and preparation method thereof
CN119877062B
